Redesigning Maternity Hospital Gowns. (2nd January 2022) - Hwang, Chanmi; McCoy, Lindsay; Shaw, Michele R.
Abstract: In the United States, maternity hospital gowns are usually designed to be a one-size-fits-all garment with full back openings that are physically and emotionally uncomfortable, immodest, and not functional. The purpose of this research is to understand the design requirements of patients and practitioners in order to redesign a functional maternity hospital gown. The researchers applied user-centered design (UCD) methods to develop a prototype based on data from market research and focus group interviews conducted in the Pacific Northwest. The researchers created a two-piece knit maternity hospital gown with an adjustable waist and a washable nursing breast pad insert system that contributes to the gown's overall fit, mobility, closure access, modesty, and tactile comfort. Through wear testing and an online survey, the new prototype was found to be successful in enhancing physical and psychological comfort throughout different stages of labor and postpartum, resulting in a novel maternity gown concept that improves current design deficiencies and addresses the needs of both patients and practitioners.